Research and Analysis of Modified Paired Transitions Algorithm Based on Fuzzy Logic in Software Defined Networks of Internet of Things - Perepelkin, Dmitry; Anisimov, Kirill (2024 International Russian Smart Industry Conference (SmartIndustryCon), 2024)
The problem of dynamic routing in a software defined networks (SDN) Internet of Things is considered, in which communication links have several quality of service (QoS) parameters. A modified paired transition algorithm based on fuzzy logic for dynamic routing to QoS ensure has been developed. A fuzzy inference system (FIS) to determine the correspondence of a communication link to a certain QoS based on the values of its parameters has been created. The linguistic variables and the base of fuzzy rules of the FIS are described. A visual environment has been developed for the experimental study of algorithms used in SDN based on fuzzy logic. Its main functions and interface are described. An experimental study of the modified paired transition algorithm based on fuzzy logic was carried out. It is shown that changing the QoS parameters of communication links leads to only a slight change in the original tree of optimal routes.